STRUKTUR DAN FUNGSI SOSIAL KEPERCAYAAN PADA UNGKAPAN LARANGAN MENGENAI MASA HAMIL, MASA MELAHIRKAN, DAN MASA KANAK-KANAK MASYARAKAT DI MINANGKABAU - Faradila Zalita; Muhammad Ismail Nasution (Jurnal Bahasa dan Sastra, 2019)
This paper contains a discussion of people’s belief in the expressions of prohibition in Kanagarian VII Koto Talago Kecamatan Guguak Kabupaten Limo Puluah Koto. This research is a qualitative by using deskriptive methods. The data of this study are the result of interviews about popular belief in expressions of prohibitions regarding pregnancy, childbirth, and childhood. After collecting and analyzing data from seven informants, there were 64 (sixty four) data about prohibition expression. The analysis of this article takes the form of social structure and function of people’s belief in the expression of prohibitions. The structure of the prohibited expression is divided into a two-part structure and a three-part structure. The social function contained in the prohibition is as education for the pregnant person. This can be seen from the door used as a place in and out the house, pregnant people should sit in the house so as not to prevent people who will go in and out the house.